Konsumsi Pemberitaan Media Online di Masa Pandemi oleh Ikatan Pelajar Riau Yogyakarta (IPRY-KB) Komisariat Bengkalis Selama Covid-19 - Fajar Kurnia Ilahi; Khairul Syafuddin (Jurnal Riset Komunikasi (JURKOM), 2021)
The limitations of movement and a lot of free time during the pandemic have an impact on each individual's media consumption. the need for news or new information in various regions makes individuals more intense in surfing various online news media. Thus, everyone's online media consumption has changed and led to new trends during the Covid-19 pandemic. The purpose of this study is to find out how the consumption of news from Ikatan Pelajar Riau Yogyakarta Komisariat Bengkalis (IPRY-KB) through online media on local news in Yogyakarta during the Covid-19 pandemic based on the media used, the duration when consuming it, to the news content that is often consumed. This research uses dependency theory, qualitative method, and purposive sampling technique by selecting 5 IPRY-KB students as informants. The results showed that IPRY-KB students' media consumption regarding local news in Yogyakarta during the Covid-19 pandemic; first, the media used are online media on a national scale and local media in Yogyakarta; second, the duration used to access news is 5 to 20 minutes; third, news about Covid-19 is the most frequently accessed and consumed topic. Reporting in online media is considered more convenient for IPRY-KB students so that they choose information sources from online media. The use of online media has also become part of the millennial generation's culture that wants fast-paced, including getting information.